2018
DOI: 10.1097/scs.0000000000004403
|View full text |Cite
|
Sign up to set email alerts
|

Craniovertebral Junction Abnormalities in Surgical Patients With Congenital Muscular Torticollis

Abstract: Our clinical experience led us to realize that craniovertebral junction (CVJ) abnormalities were common in surgical patients with congenital muscular torticollis (CMT). This study aimed to report the concurrence rate of CVJ abnormalities in surgical patients with CMT, along with comprehensive evaluation of type of concurrent CVJ abnormalities. This was a retrospective cohort study in a tertiary hospital, including 41 subjects who underwent surgical release for CMT at the mean age of 8.38 years. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Up to 18% of cases with asymmetrical head posturing may be due to non-muscular causes, 22 including Klippel-Feil, 22 neurologic disorders, 22,34 ocular disorders, 22,83,90,91 brachial plexus injuries including clavicle fractures, 22 paroxysmal torticollis that alternates sides, 24 spinal abnormalities 87,92 and SCM neoplastic masses 34,85 such as rhabdomyosarcoma. 93 Identification of presentations atypical of CMT, including masses that change shape, location, or size, warrant immediate referral to or consultation with the infant's physician.…”
Section: Supporting Evidence and Clinical Interpretationmentioning
confidence: 99%
“…Up to 18% of cases with asymmetrical head posturing may be due to non-muscular causes, 22 including Klippel-Feil, 22 neurologic disorders, 22,34 ocular disorders, 22,83,90,91 brachial plexus injuries including clavicle fractures, 22 paroxysmal torticollis that alternates sides, 24 spinal abnormalities 87,92 and SCM neoplastic masses 34,85 such as rhabdomyosarcoma. 93 Identification of presentations atypical of CMT, including masses that change shape, location, or size, warrant immediate referral to or consultation with the infant's physician.…”
Section: Supporting Evidence and Clinical Interpretationmentioning
confidence: 99%
“…The CMT group consisted of patients who had met the following 4 criteria: (1) patients who visited the Center for Torticollis, Ajou University Hospital between March 2013 and February 2017; (2) patients who have had surgery for CMT in Ajou University Hospital; (3) patients who had craniofacial CT images taken before surgery for CMT, which provided an adequate view for evaluation of the mastoid process; and (4) patients who were 15 years old or younger. Participants with CMT were managed according to the clinical pathway for CMT described in the previous report (Ahn et al, 2018). Surgery for CMT was determined when both of following surgical criteria for CMT were met: (1) significant resistance and/or limitation of the movement of the head and neck despite adequate physical therapy for 6 months or more and (2) neck MRI displaying 2 or more low-signal intensities and/or 1 large low signal intensity detectable by the naked eye within the involved SCM on T1- and T2-weighted MRI as previously described (Hwang et al, 2012; Kim et al, 2015b; Ahn et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Participants with CMT were managed according to the clinical pathway for CMT described in the previous report (Ahn et al, 2018). Surgery for CMT was determined when both of following surgical criteria for CMT were met: (1) significant resistance and/or limitation of the movement of the head and neck despite adequate physical therapy for 6 months or more and (2) neck MRI displaying 2 or more low-signal intensities and/or 1 large low signal intensity detectable by the naked eye within the involved SCM on T1- and T2-weighted MRI as previously described (Hwang et al, 2012; Kim et al, 2015b; Ahn et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have assumed that congenital trauma, perinatal compartment syndrome, and impairment of the developing SCM owing to intrauterine constraints are the main causes [ 13 ]. Additionally, secondary changes in the infant’s spine have been reported [ 14 , 15 , 16 ]. Recent studies have shown that the severity of spinal deformities in infants with CMT increases with age and with the severity of SCM tightening [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%